The role of translation in cross-cultural communication - Bukhkalo, S. I.; Ageicheva, A. O.; Shkil, S. O.; Bolotnikov, S. Yu. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The processes of translation as a separate type of communication, and examines the types of linguistic competence in the communication process that are associated with the transfer of information is studied in the article. The obstacles that arise during translation are identified, and the translation process is revealed as a result and act of communication. Practical translation methods are identified. It enables maximum improvement of translation and minimization of all difficulties arising in the translation process. The use of various methods and techniques of active learning arouses students' interest in the educational and cognitive activity itself, which enables creating an atmosphere of motivated, creative learning and at the same time solving a whole range of educational, educational, developmental tasks. It is also appropriate to add that cross-cultural competence cannot be fully utilized without the ability to conduct business negotiations, express one's opinion clearly, and also without knowledge of the general provisions of business ethics.

У статті досліджуються процеси перекладу як окремого виду комунікації, а також розглядаються види мовної компетенції в процесі комунікації, які пов’язані з передачею інформації у різновидах наукових досліджень. Виявлено перешкоди, що виникають під час перекладу, і розкрито процес перекладу як результат і акт спілкування. Визначено практичні методи перекладу. Це дозволяє максимально покращити переклад і мінімізувати всі труднощі, що виникають у процесі перекладу. Використання різноманітних методів і прийомів активного навчання викликає в учнів інтерес до самої навчально-пізнавальної діяльності, що дає змогу створити атмосферу вмотивованого, творчого навчання й водночас вирішити цілий комплекс освітніх, виховних, розвиваючих завдань. Доречно також додати, що кроскультурна компетентність не може бути повноцінно використана без уміння вести ділові переговори, чітко висловлювати свою думку, а також без знання загальних положень ділової етики.
Роль перекладу в міжкультурній комунікації
Keywords: information; communication; translation; culture; transformation; component analysis; language competence; foreign language; інформація; комунікація; переклад; культура; трансформація; компонентний аналіз; мовна компетенція; іноземна мова